An Unusual Presentation of Isolated Leptomeningeal Disease in Carcinoma of Unknown Primary With Pancreatic Features - Madhurima Anne MD; Nazish Ahmad MD; Paul Lee MD; Mohamed Aziz MD; Yehuda Lebowicz MD (SAGE Publishing, 2013)
Leptomeningeal disease (LMD) can occur in a small percentage of patients with active metastatic cancer. However, we report a case of LMD occurring during disease remission in a patient with carcinoma of unknown primary with panreaticobiliary features. A 45-year-old woman was found with mediastinal and abdominal lymphadenopathy with lymph node biopsy consistent with adenocarcinoma, expressing immunomarkers CK7, CK20, and Ca19-9 along with markedly elevated serum Ca19-9 level. The patient was started on a pancreatic cancer directed chemotherapy regimen of Folfirinox (5-fluorouracil, leucovorin, oxaliplatin, irinotecan) and achieved complete response. She was then noted to have slowly rising Ca19-9 level that did not correlate with her lack of evidence of systemic disease progression. Eventually, she presented with neurologic symptoms and was found on imaging to have isolated LMD.